Respuesta :
To find the answer, we can use the remainder theorem.
If the binomial is a factor, it will be able to divide the equation with no remiander,making the outcome = 0.
The remainder theorem is to substitute the factor into the equation.
We can try it one by one:
A.h + 2
h= -2
f(-2)=(-2)^3-8(-2)^2+19(-2)-12
=-8+32-38-12
=-24
≠0
A is incorrect.
B. h-4
h=4
f(4)=(4)^3-8(4)^2+19(4)-12
=64-128+76-12
= 0
Therefore B. h-4 is the correct answer.
Hope it helps!
If the binomial is a factor, it will be able to divide the equation with no remiander,making the outcome = 0.
The remainder theorem is to substitute the factor into the equation.
We can try it one by one:
A.h + 2
h= -2
f(-2)=(-2)^3-8(-2)^2+19(-2)-12
=-8+32-38-12
=-24
≠0
A is incorrect.
B. h-4
h=4
f(4)=(4)^3-8(4)^2+19(4)-12
=64-128+76-12
= 0
Therefore B. h-4 is the correct answer.
Hope it helps!
The answer is B) h-4 let me know if i am wrong and i am glad to help any time